The Influence of Social Media Influencers on Purchase Intention Mediated by Emotional Attachment - Yasmin Namira; Syarifah Evi Zuhra; Rizki Amalia (Yayasan Sagita Akademia Maju, 2026)
The study aims to examine the influence of Physical Attractiveness, Expertise, and Trustworthiness of social media influencers on Purchase Intention toward Bening Clinic products in Aceh, with Emotional Attachment acting as a mediating variable. The research seeks to understand how influencer credibility dimensions shape consumers' emotional connections and subsequently their intention to purchase. The study employs a quantitative approach using a survey method involving 200 respondents selected through purposive sampling. The data were analyzed using Partial Least Squares–Structural Equation Modeling (PLS-SEM) with SmartPLS 3.2.8 to test the direct and indirect relationships among variables. The findings reveal that Physical Attractiveness, Expertise, and Trustworthiness significantly influence Emotional Attachment. Expertise and Physical Attractiveness have a significant direct effect on Purchase Intention, while Trustworthiness does not directly affect Purchase Intention. Emotional Attachment fully mediates the relationship between Trustworthiness and Purchase Intention and partially mediates the relationship between Physical Attractiveness, Expertise, and Purchase Intention. The study focuses on consumers of Bening Clinic in Aceh and examines specific dimensions of influencer credibility, which may limit generalization to other regions or industries. Future research may expand the geographical scope, include additional variables such as brand image or perceived value, or compare different types of beauty clinics to enhance broader applicability. The study contributes to the influencer marketing and consumer behavior literature by integrating Emotional Attachment as a mediating variable in explaining Purchase Intention within the beauty clinic industry. The findings provide empirical evidence that emotional bonding plays a crucial role in strengthening the impact of influencer credibility on consumer purchase decisions.